Efektifitas Penerapan Sumber Belajar Biologi Model Learning Cycle pada Peserta Didik - Ashari, Rijal; Palennari, Muhiddin; Lodang, Hamka (Universitas Negeri Makassar, 2020)
Abstract.Â This development research was conducted to determine the effectiveness of Learning Resources Learning Cycle models through stages in the four D (4D) development research model proposed by Thiagrajan (1974). The type of research used is descriptive research. The research was carried out at junior high school level (SMP) precisely in Makassar VII grade VIII. The research instrument used was a learning cycle activity observation sheet and a student questionnaire response to Learning Resources. Based on the results of the effectiveness test with parametric statistical analysis between differences in class learning outcomes taught by Learning Sources the learning cycle model shows positive results compared to classes that are not taught using learning resources or conventionally, which is shown by the average corrected learning outcomes in the experimental class of 76 , 84 is higher than the class taught conventionally which is 69.82, and obtained a positive response of students by 95.83%. So from the results of the study concluded that the application of Learning Resources leaning cycle models of students provide a positive response to its application.Â Keywords:Â Learning resources, learning cycle.